Referential progression through the use of the hyponymy-hyperonymy relationship in news: focus on Portuguese language teaching-learning context - Leite, Louise Christine Oliveira da Silva; Freitas, Marília Fernanda Pereira de (The ESPecialist, 2024)
This paper focus on referential progression, using the hyponymy-hyperonymy relationship, in newspaper reports. The objective is to show how this process of resumption occurs in the conception of Textual Linguistics and to propose activities that help in the development of skills linked to referencing strategies in the understanding and production of texts, related to the use of hyponyms and hypernyms. For the bibliographical survey on referencing strategies, we used Antunes (2003 and 2005), Fávero (1998), Koch and Elias (2022), in addition to Lage (2023), for the conceptualization of the news genre. Support was also sought from the BNCC (2018), the official document that guides education in our country. Finally, a proposal for a didactic sequence based on Dolz, Noverraz and Schneuwly (2011) is presented, based on newspaper reports, in order to provide students with the ability to adequately manage referencing and referential progression, contributing to the quality of textual production.